Analisis Isi Berita Difabel di Kompas.com pada Pemilihan Presiden 2019 untuk Mendukung Media Ramah Penyandang Disabilitas pada Pilpres 2024 - Nadhiroh, S.Sos.I, M.I.Kom; Atik Nurfatmawati, SE, M.I.Kom (Kalijaga Journal of Communication, 2022)
People with disabilities need special attention, not compassion. They have their own abilities if their assistance is really maximized. Since 1992, the United Nations (UN) has designated December 3 as International Day of Persons with Disabilities. Little by little the concern and attention to the problems faced by people with disabilities is increasing. Various access more powder. One form of attention is through the news. The mass media are increasingly providing space for news reports on diffable issues. Including in the implementation of the 2019 presidential election. Efforts to support the implementation of inclusive elections continue to be increased. The mass media have a big contribution to guard support for people with disabilities. This research focuses on analyzing the news of people with disabilities in the 2019 Presidential Election at kompas.com. This research aims to examine what is the content of news about people with disabilities from the campaign period until the 2019 Presidential Election. In addition, this article is expected to be able to support disability-friendly media in the 2024 General Election The method used is to collect news about people with disabilities related to the 2019 Presidential Election which is published on kompas.com. Researchers hope that efforts to realize inclusive elections will continue to be improved as a step to fulfill the rights of people with disabilities. Orang difabel perlu mendapatkan perhatian khusus bukan belas kasihan. Mereka memiliki kemampuan sendiri jika benar-benar dimaksimalkan pendampingannya. Sejak tahun 1992, Perserikatan Bangsa-bangsa (PBB) menetapkan setiap 3 Desember diperingati sebagai Hari Disabilitas Internasional. Sedikit demi sedikit kepedulian dan perhatian kepada permasalahan yang dihadapi difabel semakin meningkat. Berbagai akses makin serbuka. Salah satu bentuk perhatian yaitu melalui pemberitaan. Media massa semakin memberikan ruang untuk pemberitaan-pemberitaan isu difabel. Termasuk di dalam pelaksanaan pemilihan presiden 2019 lalu. Upaya-upaya mendukung pelaksaanaan pemilu inklusif terus ditingkatkan. Media massa punya kontribusi besar untuk mengawal dukungan kepada para difabel. Penelitian ini fokus analisis pemberitaan difabel dalam Pilpres 2019 di kompas.com. Riset ini bertujuan mengkaji apa saja isi berita tentang difabel sejak masa kampanye sampai menjelang Pilpres 2019. Selain itu, artikel ini diharapkan bisa ikut mendukung media ramah penyandang disabilitas pada Pemilu tahun 2024. Metode yang digunakan yaitu mengumpulkan berita-berita tentang difabel terkait Pilpres 2019 yang dimuat di kompas.com secara acak kemudian menganalisis isinya. Peneliti berharap, upaya untuk mewujudkan pemilu inklusif terus ditingkatkan sebagai langkah memenuhi hak penyandang difabel.